Microbiological Profiles of Ocular Fungal Infection at an Ophthalmic Referral Hospital in Southern China: A Ten-Year Retrospective Study - Pei Y; Chen X; Tan Y; Liu X; Duan F; Wu K (Infection and Drug Resistance, 2022)
Yinhui Pei, Xiaoling Chen, Yiwei Tan, Xiuping Liu, Fang Duan, Kaili Wu State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of ChinaCorrespondence: Kaili Wu, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yan-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of China, Email wukaili@mail.sysu.edu.cn Fang Duan, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yan-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of China, Email duanfangg@126.comPurpose: This study aims to assess the testing methods used to detect fungal pathogens as well as the pathogenic profiles and drug susceptibility among fungal isolates from ocular sources collected in a tertiary eye hospital.Methods: The laboratory test records of patients with suspected ocular fungal infection from January 2010 to December 2019 at a tertiary eye care center in southern China were retrospectively evaluated. The isolated pathogens identified by smear examination and culture combined with microscopy were analyzed. For 2017– 2019 fungal isolates, their antifungal susceptibilities to four antifungal agents were evaluated.Results: A total of 22,233 specimens (16,315 for culture and 5918 for direct smear examination) from 16,209 individuals were assessed, and 3317 specimens (2169 for culture and 1148 for smear examination) from 2395 patients had confirmed fungal infection. The mean age of patients was 50.6± 14.2 years and 63.4% were male. The positive rate of smear examination was 19.4% and significantly higher than 13.3% of fungal culture (p< 0.001). Of 5812 patients who were simultaneously examined for culture and smear staining, 897 (15.43%) had positive findings for fungi. Among the 2420 positive findings, 2138 (88.3%) were from the cornea, and 133 (5.5%) were from intraocular samples. Fusarium spp. (40.5%) and Aspergillus spp. (22.0%) were the major fungal genera among the molds, whereas Candida spp. (4.6%) constituted the major yeast. Fusarium spp. had a lower antifungal susceptibility than Aspergillus spp. against voriconazole and amphotericin. And yeast spp. had the highest susceptibility to caspofungin.Conclusion: This study provided a 10-year assessment of fungi in ocular infections in southern China, giving support to epidemiological understanding and guiding empiric antimicrobial therapy.Keywords: fungal infection, eye, corneal scrape, fungal culture, keratomycosis, antifungal susceptibility, endophthalmitis